Which Peer Group to Choose? The Effects of Relative Performance Information on Employee Self-Selection and Performance - Petra Nieken; Anna Ressi (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper reports results of two controlled experiments on the behavioural effects of relative performance information (RPI) in different organizational structures. Our baseline study 1 focuses on a centralized organizational structure where employees are exogenously assigned to either a high-performing or a low-performing peer group. We find that RPI boosts performances when employees are assigned to the low-performing group. In contrast, when assigned to the high-performing group, our results point to a discouragement effect of RPI that can be attributed to low-performers. In study 2, we show that this or similarly undesired effects do not play a crucial role under a decentralized organizational structure where employees can self-select. In fact, we demonstrate that RPI especially induces employees with a relatively low performance to voluntarily choose the high-performing group. Analyzing subsequent performances suggests that providing self-selection options allows employees to use the high-performing group as a self-set target to spur motivation.
Keywords: C91; D83; D91; M52; 330; peer groups; self-selection; reference points; relative performance information